Analisis Dan Perancangan Sistem Informasi Manajemen Proyek Pada CV. Naila Fathiyah Farah - Andrian, Rafli Dicky; Sharipuddin; Joni Devitra (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
This study identifies the obstacles faced by CV. Naila Fathiyah Farah in monitoring project progress on a daily basis, mainly due to difficulties in operations and coordination between teams. Supervisors report daily data via telephone, which often causes recording errors, and the lack of project visualization reduces the effectiveness of supervision by managers. To overcome this problem, this study produces a prototype of a web-based Project Management Information System using UML (Use Case, Activity, and Class Diagram) and the Balsamiq Wireframes application. This system allows for more effective project monitoring with clearer visualization, reduces recording errors, and increases the efficiency of reporting and decision making. The main features of the system include managing employee data, clients, activities, payments, processes, documents, project teams, discussions, and reports.